Mathematical Problem Solving Ability Viewed from Extrovert Introvert Personality Types on Cooperative Learning Models Type Rally Coach - Sari, Dian Kartika; Mulyono, Mulyono; Sri Noor Asih, Tri (Universitas Negeri Semarang, 2019)
This research aims were (1) to know the quality of cooperative learning models type Rally Coach, (2) to describe students’ mathematical problem solving ability based on introvert personality type, and (3) to describe students’ mathematical problem solving ability based on extrovert personality. This study was a mixed method research with using sequential explanatory design. The population was 8th grade students of SMP N 1 Sumbang academic year 2017/2018. The subjects was selected based on extrovert personality type and introvert personality type. Data was collecting by questionnaire, observation, test, and interview. The result showed that (1) Cooperative learning models type Rally Coach was on good category (2) student with type personality introvert resolve the problem solving able to understand a problem well, plan problem solving well, carry out the problem will according to plan, and looking back for the against answer (3) student with type personality extrovert resolve the problem solving able to understand a problem well, plan problem solving well, in carry out a plan student cannot sit in an implement well that will not find correct answer, student cannot check their answer.